The job performance and job burnout relationship: a panel data comparison of four groups of academics’ job performance - Miao Lei; Miao Lei; Gazi Mahabubul Alam; Karima Bashir; Karima Bashir (Frontiers in Public Health)
ObjectivesThis present study investigates whether performance can influence job burnout, and it further examines whether there is a meaningful difference in the association between job burnout and job performance in universities. Provided here are applicable strategies aimed at preventing and maximizing job burnout crises before the job is taken and during its execution.MethodologyTo answer the research questions quantitatively, group regression analysis utilizing panel data from 2020 to 2023 was employed. The instruments include the KPI and mental health records to evaluate the level of job performance and job burnout. Likewise, a total of nine universities were purposively and randomly selected, and 1,113 academics were sampled for the study. The KPI scores and frequency of burnout counseling was collected from the human resource department and the medical health centers.FindingsThe results showed that academics’ job burnout is influenced by their job performance (β = −0.014, p < 0.001). Academics’ superior performance was notably linked to lower job burnout and the need for psychological counseling. Furthermore, academics’ job burnout was significantly moderated by psychological counseling (β = −0.006, p < 0.05), and neither did it regulate their job performance.ConclusionAcademics with high performance levels exhibit low levels of burnout. Meanwhile, academics who demonstrate low or poor performance indicate high burnout levels. Psychological counseling can moderate the level of job burnout but does not cure burnout. This study suggests that competency is the basic bedrock for strong performance and less burnout experienced by staff. Consequently, all universities should employ their staff based on assessing their competency and ability to handle stressful situations to prevent job burnout crises from occurring.ImplicationsThis paper makes a contribution to the existing literature on job performance and job burnout by utilizing a distinctive measurement path approach. In this context, universities need to use pre-measurement mechanisms to prevent burnout instead of post-measurement techniques through proactive recruitment strategies based on the popular adage that “prevention is better than cure.”